PENERAPAN ASUHAN GIZI TERSTANDAR PASIEN TUMOR MEDIASTINUM, PNEUMONIA, SINDROM VENA CAVA SUPERIOR dan HIPOKALEMIA: STUDI KASUS: Implementation of Standard Nutrition Care in Mediastinum Tumor, Pneumonia, Vena Cava Superior Syndrom and Hipocalemia Patient : Case Study - Layyinah, Hayyinatul; Rahma, Amalia (Media Gizi Pangan, 2024)
Patient have cough for 20 days. Prolonged coughing can trigger respiratory infection, one of the causes of pneumonia. Mediastinal tumor are tumor that grow in the mediastinal area between the right and left lungs. Vena cava superior syndrome is one of the clinical manifestations of a mediastinal tumor with symptoms coughing, hoarseness, shortness of breath, and edema in the face and neck area. This case study was carried out at the Muhammadiyah Lamongan Hospital for 4 days, on a patient diagnosed with a mediastinal tumor. The purpose of this study case is to gave the right nutrition intervention base on the patient condition. The principle of the diet given is high calory high protein. Before entering the hospital, patient have a decrease in appetite. The results of monitoring and evaluation showed an increase in appetite with total intake of 1440.4 kcal on the first day, 1472 kcal on the second day, 1515.9 kcal on the third day and 1493,1 kcal on the fourth day. Overall, patient energy intake has met the adequacy target